Development of an innovative cooling system at the countershaft assembly station - L.E. Espino-De la Rosa; H. Arcos-Gutiérrez; J.E. García Herrera; I.E. Garduño; J.A. Betancourt-Cantera (Applied Engineering Letters)
In automotive component manufacturing, temperature gradients are typical at workstations, especially in summer, affecting production processes. Interruptions in production lines are unacceptable, as constant flow is crucial to avoid financial losses. This issue is evident at the assembly station for the countershaft of truck transmissions, which can reach 181.7°C after welding. During summer, downtimes increase due to inadequate cooling process, as indicated by 235 minutes of downtime in May, coinciding with rising temperatures and increased demand in September, highlighting the need for an effective cooling system. This research proposes a novel design to homogenize cooling times for the countershaft. The cooling cabin was designed to fit the shaft dimensions, with air inlets strategically positioned based on assembly geometry, focusing on the hottest area. Numerical simulations using the finite element method integrated a turbulence model to analyze airflow at the cabin’s inlet and outlet. The goal was to reduce the shaft temperature from 181.7°C to an ambient range of 28°C to 34°C, minimizing cooling time and reducing downtime. Results showed a successful reduction, achieving 26.9°C.